Income-shifting arrangements, audit specialization and uncertain tax benefits, international tax risk, and audit specialization: Evidence from US multinational firms - Taylor, Grantley; Richardson, G.; Al-Hadi, Al-Hadi Ahmed (Wiley-Blackwell, 2018)
© 2018 John Wiley & Sons Ltd. The purpose of this study is twofold. First, it examines the association between income-shifting arrangements consisting of transfer pricing aggressiveness, tax haven use and foreign tax rate differentials, and Financial Interpretation No. 48 (FIN48, now ASC740-10-25) unrecognized tax benefits (UTBs). Second, it analyzes the impact of audit specialization on the association between income-shifting arrangements and UTBs. Using a dataset of 286 US multinational firms over the 2007-2016 period (2,097 firm-years), our regression results show that income-shifting arrangements represented by transfer pricing aggressiveness, tax haven use and foreign tax rate differentials are significantly positively associated with UTBs. We also observe that audit specialization magnifies the positive association between transfer pricing aggressiveness and UTBs, and foreign tax rate differentials and UTBs. Finally, in additional analysis we provide some evidence that the positive association between income-shifting arrangements and UTBs is magnified in the post-2010 uncertain tax position reporting requirement period. Overall, our study extends prior research on the topic of audit characteristics (i.e., audit specialization) and tax aggressiveness.